Integrated Pest Management Control of Varroa destructor (Acari: Varroidae), the Most Damaging Pest of (Apis mellifera L. (Hymenoptera: Apidae)) Colonies. Issue 5 (18th September 2021) - Jack, Cameron J; Ellis, James D
Abstract: Varroa destructor is among the greatest biological threats to western honey bee ( Apis mellifera L.) health worldwide. Beekeepers routinely use chemical treatments to control this parasite, though overuse and mismanagement of these treatments have led to widespread resistance in Varroa populations. Integrated Pest Management (IPM) is an ecologically based, sustainable approach to pest management that relies on a combination of control tactics that minimize environmental impacts. Herein, we provide an in-depth review of the components of IPM in a Varroa control context. These include determining economic thresholds for the mite, identification of and monitoring for Varroa, prevention strategies, and risk conscious treatments. Furthermore, we provide a detailed review of cultural, mechanical, biological, and chemical control strategies, both longstanding and emerging, used against Varroa globally. For each control type, we describe all available treatments, their efficacies against Varroa as described in the primary scientific literature, and the obstacles to their adoption. Unfortunately, reliable IPM protocols do not exist for Varroa due to the complex biology of the mite and strong reliance on chemical control by beekeepers. To encourage beekeeper adoption, a successful IPM approach to Varroa control in managed colonies must be an improvement over conventional control methods and include cost-effective treatments that can be employed readily by beekeepers. It is our intention to provide the most thorough review of Varroa control options available, ultimately framing our discussion within the context of IPM. We hope this article is a call-to-arms against the most damaging pest managed honey bee colonies face worldwide.